(untitled) (Nigerian Journal of Technology, 2018)
The effect of tempering temperature on corrosion of AISI 1045 steel in sodium chloride environment were investigated by means of weight loss measurement (WLM), optical metallography microscopy (OMM) and scanning electron microscopy (SEM) at an interval of 15 days for the period of 90 days. The results showed that corrosion of the tempered steel samples increases with increase in tempering temperatures. The corrosion rate values are between (0.0004-0.0015) g/mm²/yr for control sample which peaked on day 45, (0.0002-0.0007) g/mm²/yr for 250 oC tempered sample which peaked on day 30, (0.0003-0.0008) g/mm²/yr for 350 oC tempered sample which peaked on day 30, (0.0003-0.0012) g/mm²/yr for 450 oC tempered sample which peaked on day 30 and (0.0003-0.0013) g/mm²/yr for 550 oC tempered sample which peaked on day 30. The result obtained showed that control samples were more susceptible to corrosion in NaCl environment than tempered samples. The least tempered (250 °C) samples have better corrosion resistance than other tempered samples, which revealed that, it is best to be used in this medium compared to other tempered samples and control sample. http://dx.doi.org/10.4314/njt.v37i3.12